2010
DOI: 10.1029/2009gl042143
|View full text |Cite
|
Sign up to set email alerts
|

Thermospheric density enhancements in the dayside cusp region during strong BY conditions

Abstract: Tri‐axial accelerometer data from the Challenging Minisatellite Payload (CHAMP) satellite have revealed the thermospheric density and its variability in unprecedented detail. The data often contain regions of high density located in the cusp sector at high latitudes. In this paper we provide the first detailed explanation of a high latitude density enhancement observed by CHAMP, focusing on the August 24, 2005 interval. The Thermosphere Ionosphere Mesosphere Electrodynamics General Circulation Model (TIMEGCM) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
115
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(130 citation statements)
references
References 19 publications
15
115
0
Order By: Relevance
“…Specifically, the high latitude particle and convection forcing is specified by the Assimilative Mapping of Ionospheric Electrodynamics (AMIE) technique. AMIE assimilates magnetometer, DMSP and SuperDARN data to produce the electrodynamic specification (see Crowley et al, 2010) used by the TIME-GCM. AMIE is run at a 5 min cadence, and so the TIME-GCM is able to capture much of the variability in the forcing.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, the high latitude particle and convection forcing is specified by the Assimilative Mapping of Ionospheric Electrodynamics (AMIE) technique. AMIE assimilates magnetometer, DMSP and SuperDARN data to produce the electrodynamic specification (see Crowley et al, 2010) used by the TIME-GCM. AMIE is run at a 5 min cadence, and so the TIME-GCM is able to capture much of the variability in the forcing.…”
Section: Resultsmentioning
confidence: 99%
“…Lee et al (2010) in their recent paper entitled "Can intense substorms occur under northward IMF conditions" mention that the occurrence of such (intense) substorms implies that a certain (large) amount of energy remains in the tail even under northward IMF conditions. Crowley et al (2010) also showed that large amounts of energy can be deposited into the high latitude regions during B z northward or strong B y conditions, driving large perturbations in the neutral density at times when they would not previously have been expected. However, they argue that the energy is deposited as a result of reconnection in the lobes under B z northward or strong B y conditions, and not stored in the tail.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It remains to be seen whether the magnitude of the corresponding ionospheric ExB drift within sunward flow channels and the embedded Poynting flux directly correlates with M A in the solar wind. It is likely that sunward flow channels and enhanced Poynting fluxes exist in the ionosphere during these low M A solar wind conditions which is potentially very important for neutral density enhancements in low Earth orbit and the resulting increased satellite drag [Lühr et al, 2004;Crowley et al, 2010].…”
Section: Discussionmentioning
confidence: 99%
“…Crowley et al [2010] used the Assimilative Mapping of Ionospheric Electrodynamics (AMIE) procedure for one of these anomalous events and verified that the high 60 mW/m 2 values of localized Joule heating were present at the foot points of the near-cusp and polar cap field lines and associated them with heretofore unmodeled neutral density enhancements in this region [Lühr et al, 2004]. Knipp et al [2011] demonstrated that the same ExB flow channels examined by Eriksson et al [2008] were related to unprecedented and large earthward-directed Poynting fluxes at 850 km altitude.…”
Section: Introductionmentioning
confidence: 99%